Alternative Investments in Wealth Management A Comprehensive Study of the Central and East European Market - Sokołowska, Ewelina. (Springer International Publishing : Imprint: Springer, 2014)
This monograph provides a comprehensive source of analysis and research on alternative investments in the wealth management process, with a special focus on Poland and Eastern Europe. It presents the characteristics that distinguish alternative investments from traditional investments, and illustrates the benefits and risks involved in the former. The experience gained in developed countries is extremely valuable for the analysis of both the Polish and Eastern European financial markets. Observation of trends in other comparable countries allows us to assume, with a high degree of probability, that similar changes will take place in Poland. Moreover, it allows us to predict possible directions for the development of this market segment. In the theoretical part of the book, key aspects of alternative investments are collected, systematized and developed; subsequently, in the empirical part the results of selected studies on the alternative investment sector around the world are examined. Lastly, the book’s findings are applied to the context of alternative financial investments in Poland, investigating the preferences for alternative investments in the country, which is the largest market in Central and Eastern Europe. Not only of theoretical interest, these insights have a high application value, making the book an essential resource for scholars, practitioners and policymakers alike.